Summary of technical assistance needs for democracy and sustainable development (1993-1996) (Govt. of Guyana GeorgetownGY, 1993)
Provides brief details of the socio-economic background of Guyana as well as the urgent need for technical assistance to sustain the development thrust of the new government.
DC